Rewarding performance : guiding principles;custom strategies - Greene, Robert J. , 1940- (Routledge, 2011)
Identifies common principles that underlie sound performance and rewards management. This title explores the development and execution of 'local' performance and rewards management strategies. It addresses how programs to support the local strategies can be developed and how they can be integrated to produce alignment